(3eNJUQ eUHGM GdeJgLOs - (3eMeO Hf GdMSf GdWhSis; (3CHh LYaQ GdWhSj , CHh LYaQ eMeO Hf GdMSf Hf Ydj GdWhSj, CHh LYaQ GdWhSj,J (B460 (3g` s
(3ChdgG (B:s
(3GYdehG QMece Gddg Cfi deG YedJ YHGOI GdSfI ai GdcJGH GdPi SejJg eUHGM GdeJgLO s
(3BNQgG (B:s
(3Ke jbQC BjI GdcQSj h GdeYhPJjf h bd gh Gddg h Udi Gddg Ydi eMeO hBdg CLeYjf s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B84 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B202s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs